Driver state monitoring for intelligent vehicles - attention localization - Cai, Yuxin (Nanyang Technological University, 2022)
In recent years, there have been increasingly fundamental advances in the implementation of autonomous driving. Many autonomous driving assistance applications gradually reduce the driver's necessary driving tasks by enhancing driver-vehicle interaction, achieving a shared control scheme while improving driving comfort and safety. In order to enable the car to better understand the driver's behaviours and state characteristics, the use of computer vision techniques to detect the driver's visual attention has become a hot research topic.